Changes in the Polyphenolic Profile and Antioxidant Activity of Wheat Bread after Incorporating Quinoa Flour - José Vicente Gil; Adelaida Esteban-Muñoz; María Teresa Fernández-Espinar (Antioxidants, 2021)
Quinoa is a trend and a promising functional food ingredient. Following previous research into the impact of incorporating quinoa flour on the polyphenol content and antioxidant activity of bread, this study aimed to bridge an existing gap about the qualitative and quantitative polyphenolic profiles of such bread. The UPLC-MS/MS analysis showed that quinoa bread, made with 25% quinoa flour of a black variety, presented more compounds than refined-wheat bread, and levels were remarkably higher in many cases. Consequently, the quinoa bread presented clearly improved polyphenolic content than the wheat bread (12.8-fold higher considering the sum of extractable and hydrolyzable polyphenols), as supported by greater antioxidant activity (around 3-fold). The predominant compounds in the extractable fraction of quinoa bread were p-hydroxybenzoic acid and quercetin (50- and 64-fold higher than in wheat bread, respectively) and rutin (not detected in wheat bread), while ferulic and sinapic acids were the most abundant compounds in the hydrolyzable fraction (7.6- and 13-fold higher than in wheat bread, respectively). The bread-making impact was estimated, and a different behavior for phenolic acids and flavonoids was observed. Extractable phenolic acids were the compounds that decreased the most; only 2 of 12 compounds were enhanced (p-hydroxybenozoic and rosmarinic acid with increments of 64% and 435%, respectively). Flavonoids were generally less affected, and their concentrations considerably rose after the bread-making process (7 of the 13 compounds were enhanced in the extractable fraction) with especially noticeably increases in some cases; e.g., apigenin (876%), kaempferol (1304%), luteolin (580%) and quercetin (4762%). Increments in some extractable flavonoids might be explained as a consequence of the release of the corresponding hydrolyzable forms. The present study provides new information on the suitability of quinoa-containing bread as a suitable vehicle to enhance polyphenols intake and, hence, the antioxidant activity in daily diets.